Monitoring of Laboratory Reared of Phlebotomus papatasi (Diptera: Psychodidae), Main Vector of Zoonotic Cutaneous Leishmaniasis to Different Imagicides in Hyper endemic Areas, Esfahan Province, Iran - Leila Shirani-Bidabadi; Ali Reza Zahraei-Ramazani; Mohammad Reza Yaghoobi-Ershadi; Amir Ahmad Akhavan; Mohammad Ali Oshaghi; Ahmad Ali Enayati; Yavar Rassi; Fatemeh Gholampour; Niloufar Shareghi; Elham Madreseh; Hassan Vatandoost (Journal of Arthropod-Borne Diseases, 2019)
Background: In domestic and per domestic area,insecticides such as DDT, malathion, fenitrothion, propoxur and, more recently, synthetic pyrethroids such as deltamethrin and lambda-cyhalothrin, have been successfully used to control sand flies in many countries. The present study reports the results of time-mortality bioassay to DDT 4%, lambda-cyhalothrin 0.05%, permethrin 0.75%, cyfluthrin 0.15% and deltamethrin 0.05% in recently colonized Phlebotomus papatasi populations in Iran. Methods: The insecticide susceptibility status of P. papatasi laboratory population was assessed during 2016–2017, following the standard WHO technique for mosquito (WHO, 2013) based on diagnostic dose. Sand flies collected from rural area of Badrood (Matin Abad), Natanz County, Esfahan Province, using aspirator. Results: Susceptibility test to DDT and pyrethroids was assessed on 3534 laboratory-reared P. papatasi (1746 females and 1788 males). The LT50 and LT90 values were measured using probit analysis and regression lines. The test results against males of  P. papatasi revealed that LT50 values to DDT 4%, Permethrin 0.75%, Deltamethrin 0.05%, Cyfluthrin 0.15% and Lambdacyhalothrin 0.05% were 439.28, 108.90, 97.75, 5.00 and 57.84 seconds. The figures for females were 641.62, 136.15, 146.44, 8.71 and 72.69 seconds , respectively. Conclusion: According to presented results, the reared population of sand flies collected from a hyper-endemic region of Esfahan Province is still susceptible to prethroids and Resistance candidate to DDT 4%.